Antonio Serra and the Economics of Good Government - Patalano, Rosario; Reinert, Sophus A.; SpringerLink (Online service) (London : Palgrave Macmillan UK (Imprint), 2016)
Little is known of Antonio Serra except that he wrote his extraordinary 1613 Short Treatise on the Causes that Make Kingdoms Abound in Gold and Silver even in the Absence of Mines in a Neapolitan jail, and that he died there soon afterwards. However the contribution this work made represents a watershed not only in the discipline of economics but in the history of social science and intellectual history more generally. In this book some of the world's leading economists and experts on Serra explore the enduring appeal of Breve trattato. The authors analyse the work in its historical, economic, cultural and intellectual contexts, exploring the finer details of his theory regarding international financial interactions and his indebtedness to Renaissance legal traditions. The book also uncovers new material relating to Serra's life and provides in-depth interpretation of his key insights, influences and political economy. This book highlights the parallels between issues discussed by Serra and modern political and scholarly consciousness, and illustrates the importance and influences of historical debate in modern economic thinking.
Keywords: Finance -- History; Economic history; Italy-History.; Finance, Public